Causal association between inflammatory bowel disease and hidradenitis suppurativa: A two-sample bidirectional Mendelian randomization study - Bao, Bingzhou; Zhu, Chao; Shi, Jian; Lu, Canxing (Frontiers in Immunology, 2023)
Background: Epidemiological studies have revealed a link between inflammatory bowel disease (IBD) and hidradenitis suppurativa (HS). To determine whether IBD and HS are causally related, we used the Mendelian randomization (MR) approach. Methods: A two-sample MR was performed using an analysis of 12,882 patients and 21,770 controls with IBD and its main subtypes, ulcerative colitis (UC) and Crohn's disease (CD). A total of 409 cases and 211,139 controls without hidradenitis suppurativa (HS) were included in the data for this condition from various GWAS investigations. Odds ratios (ORs) with 95% confidence intervals (CIs) are used to estimate causal effects. Results: The study assessed the causal relationship between HS and IBD in both directions. The risk of HS was increased by IBD (IVW OR = 1.34, 95% CI = 1.20-1.49, p = 2.15E-07) and, in addition, HS was affected by UC (IVW OR = 1.27, 95% CI = 1.13-1.43, p = 8.97E-04) and CD (IVW OR = 1.18, 95% CI = 1.08-1.29, p = 4.15E-04). However, There was no evidence of a causal relationship between HS and IBD or its subtypes (IBD IVW OR = 1.00, 95% CI = 0.96-1.05, p = 0.85; UC IVW OR = 0.99, 95% CI = 0.95-1.03, p = 0.65; CD IVW OR = 1.03, 95% CI = 0.98- 1.07, p = 0.28). Conclusion: This study demonstrates that IBD and its subtypes have a causal effect on HS, whereas HS does not affect IBD. Gut-skin axis interactions may help to understand this association. Nevertheless, further studies are needed to clarify the pathophysiology of the causal relationship between IBD and HS.